THE CHILD "DIDN'T KNOW" HE WAS ADOPTED - Maggi Piccini, Amina (2012)
The article points out some of the reasons that can leadcertain adoptive parents prefer not to reveal to the child that he isadopted. However, when the decision is to keep secrets or to useuntruths in order to avoid occasional problems, others, much moresevere, can emerge, forthe parents, and above all, forthe child himself.Three cases drawn from clinical files, allow us to describe somenegative consequences, both psychological and social, mainly resultingfrom the adoptive parents insecurity in accepting themselvesserenely as such towards the child taken into their home.